The glass lake eaudiobook - Binchy, Maeve (Recorded Books Inc., 2015)
Best-selling author Maeve Binchy not only has many best-selling novels, but she is also considered to be one of the finest literary authors of contemporary women's fiction. Set in Lough Glass, Ireland, The Glass Lake is an incandescent novel of family love, belonging, and secrets that flourish in the human heart. Lough Glass is the lake at the heart of the small Irish town that bears its name. Serene and dark, its waters harbor secrets as deep and unfathomable as Helen McMahon, the beautiful woman who roams the darkened shores night after night.